Komunikasi Interpersonal Guru dan Orang Tua Siswa Bidang Perkembangan Moral Siswa Tunagrahita di Sekolah Luar Biasa Dharma Pendidikan Kecamatan Candi Kabupaten Sidoarjo - Moch Nur Cholis; Djarot Meidi Budi Utomo (Universitas Muhammadiyah Sidoarjo, 2016)
The purpose of this study was to describe the interpersonal communication of teachers and parents to the moral development of students in extraordinary school dharma, Candi Sub-districts, Sidoarjo Regency. This research used descriptive qualitative research methods. Informants in this study were teacher, parents student, and head of extraordinary school dharma, Candi Sub-districts, Sidoarjo Regency. Data collection techniques used in-depth interviews, observation, and documentation. Analyzed data used descriptive analytic based on Miles and Huberman model. The results of the study showed that communication between teachers and parents to use interpersonal communication, but had not been effective. But, teachers and parents try to did the best possible interpersonal communication in teaching hours at school and outside of school hours learning.